Palestinian resistance poetry - Praise of the High Shadow by Mahmoud Darwish as an example - A study in light of cultural criticism (Journal of the College of Basic Education, 2024)
The poetry of Palestinian resistance was an essential pillar of Arab culture, however; in the recent years, this poetry has witnessed unprecedented neglect, whether at the level of its reception and spread or at the level of its study, due to the political transformations that affected the region. The fame of the Arab-Israeli conflict faded away until it became a local conflict. While the region witnessed inter-Arab conflicts and sectarian divisions, as well as a race for normalization, in addition to other reasons that contributed to the decline of this poetic style. Today we find it important to restore its reputation as a victory for what our Palestinian Arab people in Gaza are suffering from the scourges of genocide, and to what the world is witnessing from an awakening to the Palestinian right. We found that the poem (Praise of the High Shadow) written by Mahamoud Darwish is best example of the poetry of resistance because of the connotations and images it contains that literally match with what is happening today in Gaza. This poem has been studied with multiple critical approaches, but it has not been studied culturally. Therefore, we tackled it as a basis for research in its cultural contexts and patterns.